Meningkatkan Perkembangan Motorik Halus Anak dengan Kegiatan Kolase pada Anak Usia 4-5 Tahun di TK Damhil - Wiwid Asianti Mooduto; Rini Yanti Uaneto; Masita Siyuta; Nazwa Fathlyah Makmur; Annisa Fahmi Mannassai (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This research aims to improve the fine motor skills of young children through collage using used materials at Damhil Kindergarten. This research is class A action research. The subjects of this research were 10 children, consisting of 5 children, 5 boys aged 4-5 years. The data collection technique uses descriptive qualitative techniques. The results of the research show that there is an increase in the fine motor skills of young children aged 4-5 years through collage activities. It can be explained that fine motor skills in children in Damhil Kindergarten are the child's ability to use the fingers of the right and left hand in the collage activity of applying glue to picture patterns, that is, 9 out of 10 or 90% of children are at Very Well Developed abilities while there is 1 child or 10% of children were found to be underdeveloped. Most of the children showed good mastery of fine motor skills as measured through this collage activity, although there was still one child who needed more attention.